Institutional perspectives of land reclamation operations in Punjab: a case study of the Lower Chenab Canal (East) Circle Area - Bandaragoda, Don Jayatissa; Saeed ur Rehman (International Irrigation Management Institute, 1994)
The Directorate of Land Reclamation (DLR), which was set up in 1945, is a special unit of Punjab's Irrigation and Power Department for undertaking research and field operations to combat the problem of salinity. Approaching the end of five decades of existence, the directorate is yet to demonstrate its effectiveness in its assigned task; its inability to fully cope with the conditions of a fast changing irrigation environment makes this rather an illusive goal.